2016
DOI: 10.1590/1516-4446-2016-1988
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the neural correlates of positive emotions

Abstract: Objective: To conduct a systematic literature review of human studies reporting neural correlates of positive emotions. Methods: The PubMed and Web of Science databases were searched in January 2016 for scientific papers written in English. No restrictions were placed on year of publication. Results: Twenty-two articles were identified and 12 met the established criteria. Five had been published during the last 4 years. Formation and regulation of positive emotions, including happiness, are associated with sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
(34 reference statements)
1
28
0
3
Order By: Relevance
“…; Kida and Hoshi ; Shiba et al. ; Machado and Cantilino ). The ventrolateral and ventromedial prefrontal subdivisions were activated during viewing unpleasant pictures or processing negative emotion, whereas the cortical regions were deactivated during viewing pleasant pictures or processing positive emotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kida and Hoshi ; Shiba et al. ; Machado and Cantilino ). The ventrolateral and ventromedial prefrontal subdivisions were activated during viewing unpleasant pictures or processing negative emotion, whereas the cortical regions were deactivated during viewing pleasant pictures or processing positive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that the prefrontal cortex has strong relation to emotional recognition and processing. By recording brain activity with PET and fMRI, it has been shown that the ventrolateral and ventromedial subdivisions of the prefrontal cortex are involved in the integration of emotional processing (Wager et al 2009;Grabenhorst and Rolls 2011;Seo et al 2014;Kohno et al 2015;Silvers et al 2015;Kida and Hoshi 2016;Shiba et al 2016;Machado and Cantilino 2017). The ventrolateral and ventromedial prefrontal subdivisions were activated during viewing unpleasant pictures or processing negative emotion, whereas the cortical regions were deactivated during viewing pleasant pictures or processing positive emotion.…”
Section: Prefrontal Oxygenation During Emotionally Charged Stimulationmentioning
confidence: 99%
“…Finally, the frontal lobes trigger humor appreciation through connections with these structures [14-16, 20, 29, 31, 32]. The formation and regulation of happiness seem to be associated with significant reductions in activity in the right prefrontal cortex, as well as increased activity in the VS/NA [33]. The left frontal lobe may produce a default state biased towards happy or positive interpretations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cingulate cortex plays appraisal role in subjective feeling states of pleasure and displeasure. Left superior and lateral frontal regions are implicated in regulation of both positive and negative emotions [12].…”
Section: The Fifth International Luria Memorial Congressmentioning
confidence: 99%